STUDENTS’ INTONATION IN NEWS DISCOURSE - Ika Lusi Kristanti (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2015)
Intonation plays crucial role in news discourse, mainly: in producing utterance. Speaker has to consider the intonation of his/her utterance in sentence. In this case, speaker also manages their pitch in producing the each kind of sentences.   Principally, intonation is the way of how the pitch of the voice rises and falls when we are speaking. Intonation helps or serves to determine the meaning of utterances. The utterance will be meaningless without intonation. The phenomenon encourages the writer to conduct this research on intonation in news discourse. This research emphasizes on how intonation in news discourse produced by students. This research employs descriptive qualitative research. The data of this research is spoken monologue. The data are obtained through recording the subjects while they are reading. The subjects use a microphone and laptop in recording process. The recording process applies adobe audition 3.0. In term, students’ speech production is analyzed through pitch tracks and spectrograms by using speech analyzer. Based on the findings, students produce two intonation patterns in news discourse: rising intonation pattern and falling intonation pattern. On the other hand, students use certain intonation pattern to declare information (statement/declarative sentence). Besides, there are two factors influencing production of certain intonation pattern by students in news discourse, namely: first language and knowledge